Native Wildflowers – Coreopsis lanceolata L.: ENH 147/EP058, 3/2009 - Norcini, Jeffrey G. (EDIS, 2009)
This document is about the genus Coreopsis a Florida's State Wildflower. Coreopsis lanceolata, lanceleaf coreopsis, is an evergreen to semi-evergreen perennial that is one of 14 native coreopsis species found in Florida. It primarily occurs in north Florida, but has been observed as far south as Lake County. Seed from commercial sources has been planted along roadways, although native populations are also found on roadsides. First published Dec. 1999.